The Effect of Problem Based Learning Model Assisted by Environmental Media on Concept Understanding, Reasoning Ability, and Science Problem Solving in Class V at SDN 102 Makale 5 - Anastasia Desilawaty Patoding; Nurdin Arsyad; Udan Kusmawan (EduLine: Journal of Education and Learning Innovation, 2023)
This study aims to analyze the effect of the environmental media assisted problem based learning model on concept understanding, reasoning ability and science problem solving in Class V at SDN 102 Makale 5. This research is a quantitative research with a pre-experimental research design model of one group pretest posttest design. The population in this study were all fifth grade students at SDN 102 Makale 5, totaling 99 students divided into 4 classes heterogeneously. The sample for this study was taken from four classes in the population randomly and 25 VA classes were selected as the experimental class. Data collection techniques are through tests and documentation of the process of learning activities. Based on data analysis through the pretest-post test data normality ability to understand concepts, reasoning abilities, problem solving abilities of Class V at SDN 102 Makale 5 students can be said to be normally distributed. Based on the one sample test hypothesis test on the ability to understand concepts, reasoning skills, problem solving abilities of Class V at SDN 102 Makale 5 students can be said to meet expectations, namely meeting the minimum criteria of mastery score even more than the minimum criteria of mastery learning score. Based on data analysis through the N-Gain test, it can be said that there is an increase in student learning outcomes classically in science subjects. So it can be concluded that the learning model of problem based learning assisted by media environment has an effect on increasing the ability to understand concepts, reasoning abilities, and solving science problems in Class V at SDN 102 Makale 5.